2015
DOI: 10.3928/01484834-20150717-06
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking and the Use of Nontraditional Instructional Methodologies

Abstract: The results support the utilization of nontraditional instructional (CM and PBL) methodologies in undergraduate nursing curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
2
8
0
4
Order By: Relevance
“…Correspondingly, the findings of this study are also consistent with Chen et al (), Maneval et al (), Wahl and Thompson (), Moattari et al (), and Orique and McCarthy (), who explored the effects of concept mapping in developing CT ability and the approach to learning and studying. These authors concluded that concept mapping is an effective tool for improving students’ ability to think critically.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Correspondingly, the findings of this study are also consistent with Chen et al (), Maneval et al (), Wahl and Thompson (), Moattari et al (), and Orique and McCarthy (), who explored the effects of concept mapping in developing CT ability and the approach to learning and studying. These authors concluded that concept mapping is an effective tool for improving students’ ability to think critically.…”
Section: Discussionsupporting
confidence: 92%
“…This study builds on previous work to suggest that concept mapping is an effective tool for improving students' ability to think critically (Chen et al, ; Maneval et al, ; Wahl & Thompson, ; Moattari et al, ; Orique & McCarthy, ). Using concept mapping in the education of nursing students appears to predict the development of CT skills, which is one of the most important duties of nursing education.…”
Section: Discussionmentioning
confidence: 71%
“…Both demonstrate the benefit of this association for the development of CT in students. Therefore, further studies need to be developed with the combination of different teaching strategies, since, although in this SR the strategy of concept map did not demonstrate effectiveness in the development of CT, studies have shown promising results of its association with PBL (42)(43) .…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the PBL developed as an isolated teaching strategy, studies have been conducted evaluating the use of PBL associated with concept maps (42)(43) and even in webbased learning environments (44) . Both demonstrate the benefit of this association for the development of CT in students.…”
Section: Discussionmentioning
confidence: 99%
“…Também observamos que a maioria dos estudos desenvolveu uma metodologia experimental 32,52,[106][107]109,[113][114] , o que confere um maior nível de evidência dos estudos, mas não necessariamente melhor qualidade metodológica. Uma crítica que os estudos comumente fazem é com relação à amostra de estudantes e o tempo que foi administrada a intervenção, o que nos faz refletir a respeito da dose, estratégias e modo de entrega da intervenção.…”
Section: Estratégias Para O Ensino Do Pensamento Críticounclassified